Analyses of selected heavy metals and Aflatoxin M1 in milk for human consumption in Jhang City, Pakistan - Younus, Muhammad; Abbas, Tariq; Rafique, M. Kamran; Said, Mohammed Y.; Aslam, Muhammad; Zafar, Mujahid. (International Food Policy Research Institute, 2013)
Chemical contaminants in milk affect public health and levels above permissible limits can constrain exports under sanitary and phyto-sanitary agreements. A screening survey was conducted during 2012-2013 to determine concentrations of Copper (Cu), Lead (Pb), Cadmium (Cd), Chromium (Cr), and Aflatoxin M1 (AFM1) in unprocessed, non-branded liquid milk available at conventional milk shops in Jhang city of Punjab. For the heavy metals men-tioned above, samples were also collected directly from dairy herds near a wastewater drain in suburbs of the city. Concentrations of the studied contaminants were compared between winter and summer samples.